Transnational organized crime : an overview from six continents an overview from six continents - Jay Albanese; Albanese, Jay S.; Reichel, Philip L. (Los Angeles : Sage, 2014)
This work explores the topic of transnational organised crime, incorporating expert perspectives found throughout the world's six inhabited continents: North America, Central and South America, Europe, Africa, Asia, and Oceania. Editors Jay S. Albanese and Philip L. Reichel gather the knowledge and expertise of numerous authors, researchers, and practitioners in this field who are either native to each world region, have extensively travelled and worked there, or are recognised scholars for those regions.
Transnational organized crime networks across the world / Jan van Dijk and Toine Spapens -- Transnational organized crime in North America / James O. Finckenauer and Jay Albanese -- Transnational organized crime in Latin America / Mary Fran T. Malone and Christine B. Malone-Rowe -- Transnational organized crime in Europe / Klaus von Lampe -- Transnational organized crime in Africa / Mark Shaw -- Transnational organized crime in Asia and the Middle East / Richard D. Ward and Daniel J. Mabrey -- Transnational organized crime in Oceania / Roderic Broadhurst, Mark Lauchs, and Sally Lohrisch -- Terrorism and transnational organized crime / Gus Martin.
Includes bibliographical references and index.
Keywords: Transnational crime; Organized crime; Social science -- Criminology; Organized crime; Transnational crime; Electronic books